Association of antibiotic exposure with survival in patients with extensive‐stage small cell lung cancer receiving immune checkpoint inhibitor therapy - Jiaqi Zhong; Dali Xiong; Yu Liu; Shuanghu Yuan (Thoracic Cancer, 2024)
Abstract Background Immune checkpoint inhibitors (ICIs) have dramatically shifted the therapeutic paradigm of extensive‐stage small cell lung cancer (ES‐SCLC). Antibiotic (ATB) exposure before or during ICI therapy can harm the integrity of the gut microbiome and lead to intestinal dysbiosis, which has a profoundly negative impact on the treatment response for various malignancies. Whether this is applicable to ES‐SCLC remains unclear. Methods We retrospectively reviewed the electronic medical records of all patients diagnosed with ES‐SCLC who were treated with ICI‐based immunotherapies from July 2019 to December 2020 at Shandong Cancer Hospital and Institute, China. Outcomes with the use of ATBs before or after the first infusion of ICI, including progression‐free survival (PFS) and overall survival (OS), were investigated using the Kaplan–Meier method. Multivariate analyses were also conducted using a Cox proportional hazards model. Results A total of 214 patients were included, among whom 41 (19.2%) received ATBs within 2 months before or after the first initiation of ICI therapy and were assigned to the ATB group. The ATB group showed a shorter median PFS (4.3 vs. 6.3 months; HR = 1.43, 95% CI: 0.97–2.11; p = 0.043) and a significantly shorter median OS (6.9 vs. 13 months; HR = 1.47, 95% CI: 0.98–2.20; p = 0.033) than the non‐ATB group. In the multivariate analysis, ATB exposure was markedly associated with worse PFS (HR = 1.47, 95% CI: 1.03–2.09, p = 0.035) and OS (HR = 1.46, 95% CI: 1.01–2.11, p = 0.043). Conclusions Our results demonstrate that ATB exposure was significantly associated with worse survival in ES‐SCLC patients who received ICI therapy.